Jacking in to the Matrix franchise cultural reception and interpretation - Kapell, Matthew 1969-; Doty, William G. 1939- (Continuum, 2004)
'Jacking in to the Matrix franchise', edited by Matthew Kapell and William G. Doty, is a fascinating collection of essays on the movie sensation 'The Matrix Trilogy'.
Keywords: Matrix (Motion picture); The matrix -- Film -- 1999; Beeldvorming; Films; Sociale aspecten; Darstellung; Film; Gesellschaft